Cardiothoracic surgery in the elderly evidence-based practice - Katlic, Mark R. 1951- (Springer, 2011)
Cardiothoracic Surgery in the Elderly: Evidence Based Practice is an important and timely book that reflects the thoughtful work of pioneers in geriatric surgery. It encompasses their knowledge related to geriatric surgery, and their reflections and guidance on the rapidly accumulating knowledge related to improving the health and surgical care of seniors. This book provides a scholarly review of the constantly expanding knowledge base about cardiovascular and thoracic surgery in seniors. The book follows a logical sequence covering general aspects of care, cardiac surgery and thoracic surgery. Chapters are focused on common, devastating and often missed complications of surgical care in the seniors. These include delirium, depression, pressure sores, functional losses, incontinence, volume depletion and asymptomatic or atypical complications -myocardial infarction, post-operative diarrhea, urinary track infections and pneumonia. Each is expertly reviewed. Strategies to help the surgeons and the surgical team anticipate, recognize and effectively prevent or manage such problems are discussed and the evidence basis for such strategies is provided. Cardiothoracic Surgery in the Elderly: Evidence Based Practice is particularly timely and the first to review the substantial body of knowledge that has been developed in recent years related to geriatric cardiothoracic surgical problems. It catalogs well the expanding knowledge basis for achieving successful surgical outcomes in the very old. It provides a most useful resources for cardiovascular thoracic surgeons in training and those already in practice.